Anti-inflammatory effects of asiaticoside on tumor necrosis factor-α and interferon-ᵧ Induced raw 264.7 macrophage - Zainudin, Nurfarahdilla (2016)
Centella asiatica is one of the most commonly used medicinal herbs in traditional medicine. Its beneficial effects have been attributed to its major isolated triterpene, Asiaticoside. It has been described to exhibit anti-inflammatory activities in several models. Inflammatory cells produce large amount of nitric oxide, prostaglandin E2 and cyclooxygenase. These activated macrophages functions as effectors molecules and are involved in physiological and pathological responses in neural, vascular and immune system. In this study, tumor necrosis factor-α and interferon-γ-induced inflammatory response was introduced in RAW 264.7macrophages cells to evaluate the potential effects of Asiaticoside (1.25 μM-50 μM) in these cells. Quantification of nitric oxide was determined through the Griess reaction by a microplate assay method. Prostaglandin E2 and cyclooxygenase 2 releases were quantified by EIA. To detect whether the effect of Asiaticoside on tumor necrosis factor-α and interferon-γ-stimulated RAW 264.7 macrophages cells occurred via the mitogen-activated protein kinase signal transduction pathways, western blot was performed. The results showed that Asiaticoside significantly inhibited tumor necrosis factor-α and interferon-γ -induced nitric oxide, prostaglandin E2 and cyclooxygenase-2 productions which is mediated by the suppression of the p38 mitogen-activated protein kinase signaling pathway. Based on our current findings, we concluded that Asiaticoside has anti-inflammatory effects and may be used as a therapeutic agent for the treatment of inflammation.